High Throughput Screening Platform for a FAD-Dependent L-Sorbose Dehydrogenase - Shan, Xiaoyu; Liu, Li; Zeng, Weizhu; Chen, Jian; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2020)
2-keto-L-gulonic acid (2-KLG) was a direct precursor for the production of L-Asc. Currently, the production of L-Asc in the industry was a two-step fermentation method, however, owing to many unstable factors in the fermentation process, the conversion rate of L-sorbose to 2-keto-L-gulonic acid (2-KLG) has remained at 88-90% for many years. In order to further improve the production efficiency of 2-KLG, a new type of sorbose dehydrogenase (SDH) was selected based on this laboratory, which can direct fermentation to catalyze L-sorbose to 2-KLG. Previous reported that SDH is an eventful enzyme in the metabolic pathway of D-sorbitol to 2-KLG. In this study, focused on SDH catalytic L- sorbose producing 2-KLG by optimizing the promoter, expression host screening, fermentation of temperature optimization, enhancement of related genes, knocking out possible related by-product genes, and mutation screening, to construct a superior high-throughput screening platform suitable for improving 2-KLG production; The results have an important reference value to enhance the metabolic pathway of E. coli to produce 2-KLG.